2004
DOI: 10.1159/000079115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pregnancy Outcomes of Progesterone or Progesterone + Estradiol for Luteal Phase Support in ICSI-ET Cycles

Abstract: Objective: To find out the effect of estradiol with progesterone for luteal phase support in IVF-ICSI cycles. Materials and Methods: Patients were accepted for treatment in the ART unit of Selcuk University, Meram Faculty of Medicine, between January 2001 and March 2003. The study was done in a prospective manner. The age range of 252 women was 19–41 years and the total number of cycles was 310. All patients were treated with a long ovulation induction protocol. Patients were treated and divided into two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 34 publications
0
21
0
3
Order By: Relevance
“…However, multiple cycles of IVF treatment from the same patients were included in the study without adjusting for the clustering of multiple cycles within the same subject. It is interesting to note that other randomized studies that have found significant improvement in pregnancy rates after E 2 supplementation have included multiple cycles from the same patient without the appropriate statistical adjustments (4)(5)(6)(7). In this current study, we included only one cycle of treatment from each patient to exclude the bias of the correlation between multiple cycles.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple cycles of IVF treatment from the same patients were included in the study without adjusting for the clustering of multiple cycles within the same subject. It is interesting to note that other randomized studies that have found significant improvement in pregnancy rates after E 2 supplementation have included multiple cycles from the same patient without the appropriate statistical adjustments (4)(5)(6)(7). In this current study, we included only one cycle of treatment from each patient to exclude the bias of the correlation between multiple cycles.…”
Section: Discussionmentioning
confidence: 99%
“…The use of hCG also doubled the risk of ovarian hyperstimulation syndrome (OHSS) compared with the use of progesterone (7). Other RCTs have shown that the addition of estrogen to progesterone in the luteal phase following a long GnRHa protocol further improves implantation rates (9,10).…”
mentioning
confidence: 99%
“…The exclusion criteria were the following: [1] an hCG day E 2 level above 3,000 pg/mL (because of ovarian hyperstimulation syndrome [OHSS] risk), [2] diminished ovarian reserve (FSH >12 IU/mL), [3] endometriosis greater than stage II, [4] severe male factor (<5 million motile spermatozoa per milliliter requiring testicular sperm extraction, [5] endocrine disorders, [6] polycystic ovary syndrome, or [7] frozen-thawed cycles.…”
Section: Materials and Methods Patient Populationmentioning
confidence: 99%